Given that x , y , z satisfy the following system of equations:-
⎩ ⎪ ⎨ ⎪ ⎧ x + y 1 = 3 7 y + z 1 = 4 z + x 1 = 1
What is the value of x y z ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
A very nice way to solve this problem!
i just use my intuition and its right xD
i`m so lucky hahaha xD
Nice and simple.
You have two approaches to deal with such problems :
1-The easy non-frustrating approach
2- The long hard to solve approach
let's begin with the easy non-frustrating one first :
By multiplying the equations : ( x + y 1 ) ( y + z 1 ) ( z + x 1 ) = ( 3 7 ) ( 4 ) ( 1 )
x y z + y + x + z 1 + z + x 1 + y 1 + x y z 1 = 3 2 8
Looks pretty scattered , doesn't it ? let's give it some order
x y z + x y z 1 + ( x + y 1 ) + ( y + z 1 ) + ( z + x 1 ) = 3 2 8
x y z + x y z 1 + 3 7 + 4 + 1 = 3 2 8
x y z + x y z 1 = 3 6 = 2
Multiplying by x y z
( x y z ) 2 − 2 ( x y z ) + 1 = 0
x y z = 1
As For the other approach , It basically counts on finding the value of x , y , z , but I'll solve it by finding only one of them
We Begin it by multiplying the first equation by y :
x y + 1 = 3 7 y
x y = 3 7 y − 1 → ( 1 )
We'll need this one , but not now
Back to the first equation :
x = y 1 − 3 7 y = 3 y 7 y − 3
Use this to substitute x in the third equation :
z + 3 y 7 y − 3 1 = 1
z + 7 y − 3 3 y = 1
And in the second equation :
z 1 = 4 − y ⟺ z = 4 − y 1
∴ 4 − y 1 + 7 y − 3 3 y = 1
After simplifying , it should be like this :
4 y 2 − 9 y + 1 2 = 0 ( 2 y − 3 ) 2 = 0 y = 2 3
We have every thing in need . now , Let's get to what we want :
Back to the third equation and multiply it with x y :
x y z + y = x y
From (1) :
x y z + y = 3 7 y − 1
x y z = 3 4 y − 1
x y z = 3 ∗ 2 4 ∗ 3 − 1
x y z = 1
very nice solution....
amazing :)
I tried solving it by just substituting valus ._.
after the easy one, you type "As For the other approach , It basically counts on finding the value ofxyz , but I'll solve it by finding only one of them We Begin it by multiplying the first equation by y :" you form an equation" xy=7y/3-1" but after that you type "We'll need this one , but not now Back to the first equation :" there the first equation is give wrong ............you have given "x=1/y-7y/3" but the correct one can be seen on the question ie. x=-1/y+7/3 and therefore the whole ans after that is wrong
Well i din't find the value of x, y & z but found the ans the other way..
Multiplying equation 1, 2 & 3..
Later simplifying we get an equation
xyz+x+y+z+1/x+1/y+1/z+1/xyz=28/3
Again simplifying & considering a=xyz
We get, a^2-2a+1=0
Rest is simple..
⎩ ⎪ ⎨ ⎪ ⎧ x + y 1 = 3 7 y + z 1 = 4 z + x 1 = 1 ( 1 ) multiplying 1st and 2nd members of the equations of system 1 :
( x + y 1 ) ( y + z 1 ) ( z + x 1 ) = 3 2 8 , ( 2 )
x y z + y + x + z 1 + z + x 1 + y 1 + x y z 1 = 3 2 8 , ( 3 )
now introducing ( 1 ) in ( 3 ) :
x y z + x y z 1 = 3 2 8 − 3 7 − 4 − 1 = 2 , ( 4 ) denoting x y z = t , t = 0 , ( 4 ) become:
t + t 1 = 2 , ( 5 ) t 2 − 2 t + 1 = 0 , ( 6 ) ( t − 1 ) 2 = 0 , ( 7 ) equation. ( 7 ) has solution: t = x y z = 1
x + 1/y = 7/3 x = 7/3 - 1/y = (7y-3)/3y
z + 1/x = 1 z = 1 - 1/x = 1 - 3y/(7y-3) = (4y - 3)/(7y - 3)
y + 1/z = 4 y = 4 - 1/z = 4 - (7y - 3)/(4y - 3) y = (9y - 9)/(4y - 3)
Cross-Multiplying and simplifying we get: 4y^2 - 12y + 9 = 0 Therefore, y = 3/2
Using the value of y, we get x = 5/3; z = 2/5
x y z = 5/3 * 3/2 * 2/5 = 1
z = 1 − 1 / x = ( x − 1 ) / x , y = 4 − 1 / z = ( 4 z − 1 ) / z , ( 4 z − 1 ) / z − x / ( x − 1 ) , 1 / x = 1 − z , x = 1 / ( 1 − z ) , 1 / ( 1 − z ) + z / ( 4 z − 1 ) = 7 / 3 < = > ( 4 z − 1 ) + z ( 1 − z ) = ( 7 / 3 ) ( 1 − z ) ( 4 z − 1 ) < = > − z 2 + 5 z − 1 = ( 7 / 3 ) ( − 4 z 2 + 5 z − 1 ) < = > 3 ( − z 2 + 5 z − 1 ) = 7 ( − 4 z 2 + 5 z − 1 ) 2 5 z 2 − 2 0 z + 4 = 0 ( 5 z − 2 ) 2 = 0 z = 2 / 5 1 / x = 1 − 2 / 5 = 3 / 5 x = 5 / 3 y = ( 8 / 5 − 1 ) / ( 2 / 5 ) = ( 3 / 5 ) / ( 2 / 5 ) = 3 / 2 x y z = 2 / 5 ∗ 5 / 3 ∗ 3 / 2 = 1
first find out the value of z from 3rd equation and value of y from 1st equation and substitute the values of y and z in 2nd equation you will get the equation 9X^2 - 30X + 25= 0 so we get X= 5/3 now put the value of x in third equation we get z = 2/5 and from first equation we get y = 3/2 and Hence XYZ = (5/3)(3/2)(2/5)= 1
Problem Loading...
Note Loading...
Set Loading...
By multiplying the three equations:
(xyz + y + x + 1/z + z + 1/x + 1/y + 1/xyz) = 28/3
xyz + 1/xyz = 2
then
xyz = 1